Epidemiological characteristics of amebiasis in Japan from 2001 to 2022 - Keisuke Iida; Hirotake Mori; Dmytro Remez; Daria Krokva; Yoshiro Hadano; Aongart Mahittikorn; Toshio Naito (PLoS ONE, 2026)
Amebiasis cases in Japan are reported to the government according to the Infectious Diseases Control Law. Previous studies have shown significant reductions in total case numbers after 2018 and during the COVID-19 pandemic. This study aimed to clarify the recent trends of amebiasis cases in Japan, including during the pandemic period, with details on places of infection, using government surveillance data from January 1, 2001, to December 31, 2022. Change of time trends were modeled through piecewise mixed-effect regression model with knots set at 2018 and 2020. Year-to-year differences in case numbers were statistically assessed using Poisson regression model. And descriptive analyses of amebiasis cases reported in Japan by sex, age class, and prefecture (from 2001 to 2022) were conducted. Piecewise time trends of male-domestic cases showed increasing trend by 59.5 cases per year (p < 0.0001) before 2008. The trend slowed but still increased during 2008–2018, showing annual increase of 15.2 cases per year (p = 0.0014). A sharp decline occurred during 2018–2020, with cases decreasing by 219.0 cases per year (p < 0.0001). After 2020, the trend did not show statistically significant change (−16.9 cases per year, p = 0.6532). Poisson regression confirmed significant reductions in total and domestic cases between 2017–2018 and 2019–2020, while imported cases declined significantly only between 2019 and 2020. Male cases predominated, with most male cases in their 40s and 50s. Most cases of amebiasis have been reported in metropolitan areas. These results suggest that the decreased case numbers during the COVID-19 pandemic were due to not only the travel ban, but less socioeconomic activity. Furthermore, the epidemiology of amebiasis is similar to that of HIV infection in Japan, but the case numbers of amebiasis have not yet increased through 2022, showing a different trend from HIV infection and syphilis, the reason of which is unclear and needs further investigation.